Geographical Inquiry: Learning Model to Empower Students' Spatial Citizenship in Higher Education - Singgih Prihadi; Novika Adi Wibowo (Universitas Negeri Gorontalo, 2025)
This research was initiated by the lack of spatial citizenship in geography learning from secondary to tertiary levels, even though this is crucial for becoming citizens with a spatial perspective. This study aims to develop an effective geography learning model to improve students' spatial citizenship. This study used the design-based research method, which has four stages: analysis of practical problems, design development, implementation, evaluation, and reflection. The research subjects were 250 students of Geography Education at Sebelas Maret University for needs analysis and 27 for product effectiveness testing. Data collection techniques were classroom observation, in-depth interviews, tests, expert judgment, and focus group discussions, testing the effectiveness using a one-group pretest-posttest design. The data analysis technique at the practical problem analysis stage was a constant comparative method. The geographical inquiry model is efficacious in improving students' spatial citizenship skills. Calculation of the paired sample t-test shows the value of Sig. (2-tailed) 0.05, so there are differences in learning outcomes using the geographical inquiry model in improving spatial citizenship skills. This geographic inquiry model effectively provides essential steps in conducting geographic inquiries to solve problems using geospatial data sources. This study concludes that if geographical inquiry is applied appropriately and comprehensively in geography education at the university level, it will provide students with the skills to become good citizens from a spatial perspective. For further research, it is hoped that applying the geographical inquiry model with a deep learning approach to geography learning can be studied